A Comparison Study on the Carbon Corrosion Reaction under Saturated and Low Relative Humidity Conditions via Transmission Line Model-Based Electrochemical Impedance Analysis. Issue 6 (21st June 2021) - Kwon, JunHwa; Choi, Pilsoo; Eom, KwangSup
Abstract : In this work, we study the dependence of water content on the carbon corrosion reaction by applying an external potential (1.4 V vs RHE) under saturated and low (30%) relative humidity (RH) conditions via a transmission line model (TLM)-based impedance analysis in a polymer electrolyte membrane fuel cell (PEMFC). High potentials inducing carbon corrosion reaction cause electrode thinning, make the supporting carbon structure less porous, decrease the electrochemical surface area (ECSA), and dehydrate the ionomer, leading to fast performance decay in the cell. Particularly, in this work, we discuss the main cause of performance decay in PEMFCs in view of the structural deformation of supporting carbon using the ionic resistance and double layer capacitance in non-faradaic impedance and charge transfer resistance in faradaic impedance to elucidate the different degradation behaviors of membrane electrode assembly (MEA) under saturated and low humidity (RH 30%) conditions. As a result, it is confirmed that carbon corrosion severely changes the structural properties of the supporting carbon, such as pore depth and circumference, and the specific pore deformation with the evolution of oxygen-containing functional groups on the carbon surfaces subordinately induces the severe degradation in cell performance with the water drainage issues, namely, flooding.